Diffusion model-based understanding of subliminal affective priming in continuous flash suppression - Minchul Kim (Nature Portfolio, 2021)
Abstract Affective states influence our decisions even when processed unconsciously. Continuous flash suppression (CFS) is a new variant of binocular rivalry that can be used to render the prime subliminal. Nonetheless, how prior information from emotional faces suppressed by CFS influences subsequent decision-making remains unclear. Here, we employed a CFS priming task to examine the effect of the two main types of information conveyed by faces, i.e., facial identity and emotion, on the evaluation of target words as positive or negative. The hierarchical diffusion model was used to investigate the underlying mechanisms. A significant interaction effect on response time was observed following the angry face prime but not the happy or neutral face primes. The results of the diffusion model analyses revealed that the priming effects of facial identity were mapped onto the drift rate and erased the ‘positive bias’ (the processing advantage of positive over negative stimuli). Meanwhile, the positive emotional faces increased the nondecision time in response to negative target words. The model-based analysis implies that both facial identity and emotion are processed under CFS.